Oxytocin system social function impacts in children with attention-deficit/hyperactivity disorder - ERDOĞDU, AYŞE BURCU (WILEY, 2015)
To investigate relationships between the polymorphisms and social functioning of children with Attention Deficit/Hyperactivity Disorder (ADHD), according to the polymorphism of three oxytocin receptor (OXTR) genes (rs53576, rs13316193, and and rs2268493). A total of 198 childrenstudying in the same primary and secondary school and matched in terms of age and gender (99 ADHD, 99 control)were included in this study. The Schedule for Affective Disorders and Schizophrenia for School-Age Children-Present and Lifetime Version was administered to establish the clinical diagnosis. The Social Reciprocity Scale (SRS) was applied to evaluate social functioning. The total genomic DNA was isolated from buccal mucosa samples. No significant differences were determined between the ADHD and control groups in terms of rs2268493, rs13316193, and rs53576 genotype distribution (P=0.078, P=0.330, and P=0.149, respectively). However, the control group T allele frequency in the OXTR Single Nucleotide Polymorphism (SNP) rs2268493 was significantly higher than the ADHD group (P=0.024). Compared to the control group, the ADHD group had a higher score on the SRS scale (SRS total; Z=-21,135, P<0.001). No significant difference existed in the SRS scale scores between the children with the T/T genotype and the C allele in the ADHD group (SRS total; Z=-0.543, P=0.587). The allele distribution of the OXTR gene SNP rs2268493 was significantly different in the ADHD group, compared to the control group. This observation is important in understanding the underlying biological infrastructure in ADHD and developing treatment modalities. (c) 2015 Wiley Periodicals, Inc.
Keywords: oxytocin receptor; gene; polymorphism; ADHD; child; RECEPTOR GENE OXTR; COMMUNICATION-CHECKLIST; AUTISM; ASSOCIATION; BEHAVIOR; SUPPORT; ADHD